العنف في وسائل الإعلام ، مظاهره وطرق مواجهته - دليو, الأستاذ الدكتور: فضيل (Sciences de l'Homme et de la Société; Vol. 14 (2015): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ(Mars), 2015)
لا زالت مسألة العنف في وسائل الإعلام حديث الساعة، فهي ظاهرة متجددة تطفو على الساحة العامة كلما حدث حادث عنيف في الحياة الحقيقية وخاصة إذا كان فاعلوه من الأطفال. فيتسارع إلى مناقشة مدى ارتباطه بما ينشر أو يبث في وسائل الإعلام. بداية يجب الإشارة إلى أن النقاش المثار حوله لا يكون دائما ذي خلفيات علمية محضة، وذلك بدء بتحديد ما هو عنف مما هو ليس كذلك وانتهاء إلى مدى تأثير الإعلامي منه على الجمهور.   Abstract : The topic of "Violence in mass-media" is very important and specially when the consumers are adolescents.  It is quickly related to the role of the mass-media in preventing and confronting violence in our societies. The study starts with defining concepts of violence in general and concretely in the mass-media, then it exposes the problematic of this phenomenon, which personal and social characteristics are related to the exposure to violent audiovisual contents, and finally it discusses how to enhance the role of our different institutions in fighting against the violence of the torrent of images and sounds overwhelming our lives. At last, the study recommends some suggestions which turn basically around how to make our relation with the mass-media efficient.